A framework for development of real-world motorcycle driving cycle in India. (May 2021) - Sithananthan, Masilamani; Kumar, Ravindra
This paper proposed a framework for development of real-world driving cycle in India after a thorough review and comparison of motorcycle driving cycles used in different countries. A limited state-of-the art work for the development of driving cycles for motorcycles is available. The motorcycle driving cycles developed by different countries differ from each other in terms of their driving cycle characteristics, emission factors, and fuel economy. This paper reviewed the parameters of real-world driving cycles of motorcycles and compares the same with legislative cycles concerning their characteristics and emissions. The parameters of real-world driving cycles and Indian legislative cycle (IDC) deviate significantly from other legislative cycles in the range of −97% to +1172% and −74% to 284% respectively. The emission factors of the legislative cycle do not match with the realistic emissions measured by real-world driving cycles. This is due to the reason that the legislative cycles do not represent the current traffic scenario and hence need to be revised. A framework is proposed to develop a real-world driving cycle in India.